Atomic structure activities for secondary science - Miller, David W. (My University, 2013)
Section One - The Development of a New Atomic Model and the Rutherford Gold Foil Activity Students who performed the Rutherford gold foil activity simulated Ernest Rutherford's famous gold foil experiment. In this activity students determined the shape of two different irregularly shaped objects utilizing a ball bearing rolling down a ruler. By rolling a ball bearing down a ruler students found that the vast majority of times the ball bearing passed straight past an object hidden under a platform. This activity helped to confirm that most of the atom is made up of empty space with a small portion of the atom being that of a small positively charged nucleus. Section Two - Quantum Model of the Atom and Schrodinger's Electron Probability Activity During the Schrodinger's Electron Probability activity students used marbles and a target to investigate the three-dimensional distribution of the electron in the ground state orbital of hydrogen. This two-dimensional model that students created helped them to better understand the three-dimensional distribution of an electron in the ground state orbital of hydrogen. Section Three - Electron Configurations and the Electron Battleship Activity This lab activity gave students the opportunity to learn the noble gas and standard electron configuration notations of atoms in their ground state. Students worked in pairs of two and played a game called Electron Battleship. The goal of the game was to place all five ships on the periodic table hidden from their opponent's view keeping them from being destroyed. Each player kept track of their own ships and their opponent's ships by using different laminated periodic tables. The first player flipped a penny; if the penny was tails then the first player gave the electron configuration using the noble gas notation. If the penny was heads then the first player gave the electron configuration using standard notation. This allowed practice for both methods of naming the electron configuration of an atom.
Plan B Paper. 2013. Master's of Science Education. Physics Department. 45 leaves. Includes bibliographical references (leaves 36-37).
Keywords: Physics--Study and teaching (Secondary)--Activity programs; Physics--Study and teaching (Secondary)